The Planning System of Peru and its Impact on Socio-Economic Development - Valeriano Ortiz, Luis Fernando (2019)
This article focuses on the development of Peru’s planning system and its impact on socio-economic developments with respect to the factors of the international (globalization) and national macro environment (sectors that include non-renewable resources such as minerals and renewable (such as agro industry, textile, etc.) and its political, economic, social, regulatory, cultural, tourism, environmental, technological factors (patents and intellectual property) etc. And its micro environment, such as the behavior of the national market (supply and demand) with their respective development indicators. In every society and particularly in our country the most important intangible is the human talent formerly called human resource (cognitive skills, soft and emotional skills, leadership, creativity and innovation). With greater reason in emerging countries like ours, where governments must generate a climate of political, social and economic stability of social inclusion, with a quality education, betting on the development of innovation and creativity, zero tolerances to insecurity citizen and have a promoting role of social responsibility and entrepreneurship, key factors for the development of Peru. In a globalized world, in which information and communications technologies are constantly modernized, such as their internet tools, intranet, social networks, virtual platforms, computer programs, etc., generate the need for sectors to be integrated into a system of national information. All this will be possible if immorality is fought from all fronts, which creates distrust and lack of credibility in its authorities.